MODEL IMPLEMENTASI KULIAH KERJA NYATA TEMATIK PENUNTASAN BUTAAKSARA UNIVERSITAS NEGERI SEMARANG TAHUN 2008 DI KECAMATAN BANDAR KABUPATEN BATANG - Setiaji, Khasan (Universitas Negeri Semarang, 2010)
TheKKNTematik PBA(illiteracy eradication field program) is a collaborativeprogram between provincial governments and universities to irradicate illiteracy inCentral Java. Semarang State University was one of the universities taking a part inthe program. The program was conducted among other in Bandar Batang.participants responses and their achievement in basicmath, reading, and writing. The subject of the study was the implementation of themodels the program in Bandar Batang in 2008. The models consisted of three: private,small group, and large group. The population (226 people) was selected through adisproportionate stratified random sampling of 5 villages. The variables of theresearch were participants responses and their achievement. The data were collectedwith a questionnaire and document analysis. The data were analyzed with descriptiveanalysis of the percentage and chi-square analysis. It was revealed that the response ofthe participants fell under good category. The achievement of the participants in basicmath, reading, and writing fell under low category.kata kunci: KKNtematik, buta aksara, warga belajar